Sizing of a Photovoltaic Solar Plant on Campus II of UFVJM in Diamantina, Minas Gerais (International Journal of Geoscience, Engineering and Technology, 2023)
The constant growth of technology has increasingly demanded a better energy matrix. As a result, new, more efficient ways of generating energy have been created. Among all, photovoltaic solar energy is increasingly gaining space in the market due to its efficiency and low impact on the environment. In the present work, the design of a photovoltaic solar plant on Campus II will be calculated, through an on-grid system. For this, it was necessary to obtain the electricity bills of Campus II between the period of 2016 and 2022. After collecting and calculating the energy demand of Campus JK, it was possible to obtain the best type of photovoltaic solar module and frequency inverter. Thus, the design of a photovoltaic solar plant that supplies all the energy demand of Campus JK was carried out.